The hunchback of Notré-Dame - Hugo, Victor, 1802-1885 (The modern library, 2002)
In fifteenth-century Paris, a disfigured man named Quasimodo, who was abandoned as an infant in the cathedral of Notre-Dame and now lives in its bell tower, must come to the aid of a beautiful gypsy girl named Esmeralda after she repels the advances of the cruel archdeacon Don Claude Frollo.